MEA degradation and failure modes in PEM fuel cells - Silva, R. A. (2009)
The mechanisms of fuel cell degradation are not well understood. Even though the numbers of installed units around the world continue to increase and dominate the pre-markets, the present lifetime requirements for fuel cells cannot be guarantee, creating the need for a more comprehensive knowledge of material’s ageing mechanism. In this work, failure modes and mechanism of the membrane-electrode assembly (MEA) in PEM fuel cells are studied stressing the issues that may constrain stability, power and lifetime. Diagnostics methods and tools used for in-situ and ex-situ analysis of PEM fuel cells were used in order to better categorize irreversible changes in the kinetic and/or transport properties of the cell. Data for MEA degradation obtained during and after fuel cell ageing in extreme testing conditions will be discussed. Electrochemical Impedance Spectroscopy (EIS) is found instrumental in the identification of fuel cell flooding conditions and membrane dehydration associated to mass transport limitations / reactant starvation and protonic conductivity decrease, respectively. Cross sections of the membrane catalyst and gas diffusion layers examined by scanning electron microscopy indicate electrode thickness reduction as a result of ageing. Catalyst particles are found to migrate outwards and located on carbon backings. Nafion degradation in fuel cell environment is analysed in terms of the mechanism for fluoride release which is considered an early predictor of membrane degradation. The application of a full range of diagnostic techniques and modelling is felt necessary in order to aid design and operating strategies in PEM fuel cells.